Pengaruh Kualitas Pelayanan dan Kepuasan Pasien terhadap Loyalitas Pasien Rawat Jalan Di RSIA Kartini Padalarang - Sania Septiani Surachman; Fransiska Agustina (Universitas Nusantara PGRI Kediri, 2023)
Outpatient services are very important services because outpatient services are the first source of health services for patients in need, being a place for follow-up of patient conditions, continuous routine nurses and carrying out intermediary functions by becoming the first referral center for hospitals and services. other health. The population in this study were 250 patients at RSIA Kartini Padalarang, West Bandung. The sample in this study amounted to 154 respondents. The research method used is descriptive quantitative to get an overview of the influence between variables, namely Service Quality, Patient Satisfaction and Patient Loyalty RSIA Kartini Padalarang West Bandung. Based on the determination test, it is known that Service Quality and Patient Satisfaction have an effect of 0.196 or 19.6% on Patient Loyalty. This figure shows that the influence of variables X1 and X2 on variable Y simultaneously, while the remaining 80.4% is influenced by other variable factors outside of this study or error values. Based on the F test that the F value is greater than the F table value (19.603 <3.06), in other words a significance of 0.000 <0.05. This means that the two variables of Service Quality and Patient Satisfaction have a significant effect on Patient Loyalty.